2019
DOI: 10.3389/fpsyg.2019.01754
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Working Memory on Dual-Task Cost During Walking Performance in Childhood

Abstract: This study examined the effect of a secondary motor task on walking ability, whether performance differed according to age and the possible relationship between cognitive abilities, specifically working memory, and dual-task costs in children with typical development. Fifty-three female children (mean age M = 10 ± 2 years), were divided into two different age groups: a young (7–9 years; n = 17) and an older group (10–13 years; n = 36). First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Five studies use a sample type not making comparisons between groups (Beurskens et al, 2016;Asai et al, 2014;Nordin et al, 2010;Tang et al, 2015;Liu et al, 2018). One study examined the effect of a secondary motor task on walking ability in childhood (Rabaglietti et al, 2019).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies use a sample type not making comparisons between groups (Beurskens et al, 2016;Asai et al, 2014;Nordin et al, 2010;Tang et al, 2015;Liu et al, 2018). One study examined the effect of a secondary motor task on walking ability in childhood (Rabaglietti et al, 2019).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In most studies, the principal motor task analyzed was gait (Beurskens et al, 2016;Abbruzzese et al, 2014;Asai et al, 2014;Beurskens & Bock, 2013;Nordin et al, 2010;Oh-Park et al, 2013;Júnior et al, 2017;Mofateh et al, 2017;Baldan & Elmauer, 2015;Liu et al, 2018;Hunter et al, 2018;Kachouri et al, 2019;Rabaglietti et al, 2019).…”
Section: Description Of Motor Tasksmentioning
confidence: 99%
“…Particularly, in primary school-aged children, working memory performance has been shown to predict academic performance such as the performance in mathematics [11]. In addition, working memory is related to dual task performance in life activity [12]. Therefore, working memory has important roles not only in academic performance, but also in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this research has indicated that executive functions play an essential role for keeping postural control when walking (Springer et al, 2006; Woollacott & Shumway-Cook, 2002; Yogev-Seligmann et al, 2008), to date, there are no studies that explored this relation between walking and all three core components of executive functions in much detail. Previous work has focused on correlating dual-task performance with only one core component of executive functions (e.g., working memory in Rabaglietti et al, 2019; inhibition in Springer et al, 2006 and Yogev et al, 2005). However, none of the previous studies has included all three executive-function components in a combined design.…”
mentioning
confidence: 99%
“…Dual-task studies indicated that walking performance in a dual task correlated with executive functioning in a sample of typically developing 7-to 13-year-old children (Rabaglietti, De Lorenzo, & Brustio, 2019), older participants with a higher risk to fall (Springer et al, 2006), or patients with Parkinson's disease (Yogev et al, 2005). Further evidence came from infant studies in which novice walkers showed more perseverative behavior in a locomo-tor A-not-B task as compared to experienced crawling infants (Berger, 2010).…”
mentioning
confidence: 99%